Physiological importance and role of Mg2+ in improving bacterial resistance to cesium - Ishida, Yoshiki; Zhang, Chongkai; Satoh, Katsuya; Ito, Masahiro (Frontiers in Microbiology, 2023)
Cesium (Cs) is an alkali metal with radioactive isotopes such as 137Cs and 134Cs. 137Cs, a product of uranium fission, has garnered attention as a radioactive contaminant. Radioactive contamination remediation using microorganisms has been the focus of numerous studies. We investigated the mechanism underlying Cs+ resistance in Microbacterium sp. TS-1 and other representative microorganisms, including Bacillus subtilis. The addition of Mg2+ effectively improved the Cs+ resistance of these microorganisms. When exposed to high concentrations of Cs+, the ribosomes of Cs+-sensitive mutants of TS-1 collapsed. Growth inhibition of B. subtilis in a high-concentration Cs+ environment was because of a drastic decrease in the intracellular potassium ion concentration and not the destabilization of the ribosomal complex. This is the first study demonstrating that the toxic effect of Cs+ on bacterial cells differs based on the presence of a Cs+ efflux mechanism. These results will aid in utilizing high-concentration Cs+-resistant microorganisms for radioactive contamination remediation in the future.